La Traduction Automatique de “We Should all be Feminists”: Une Etude Critique - Amaka Udogu, Cheryl (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
Résumé Au fil du temps, il y avait un courant de pensée qui croit qu’un jour, la traduction automatique remplacera la traduction humaine. Cela engendre la peur chez les traducteurs. À cause de cela, nous avons décidé de faire une comparaison entre une traduction humaine, un extrait de la traduction française de «We should all be feminists » de Chimamanda Ngozi Adichie et sa traduction automatique. Suite, il y aura une analyse et comparaison de la traduction humaine et la traduction selon deux logiciels de la traduction, utilisant la théorie linguistique de la traduction comme modèle, pour arriver à une conclusion pertinente. Mots clés : traduction automatique, traduction humaine, comparaison, linguistique, Abstract Over time, there has been a school of thought that believes that machine translation will one day, replace human translation. This has created fear in the hearts of translators, especially student translators. Due to this fact, we have decided to carry out a comparative study between the French human translation of We should all be feminists by Chimamanda Ngozi Adichie and its machine translation. We did a comparison and analysis of the human translation and two machine translations using the linguistic theory as a guide to reach a viable conclusion. Keywords: Computer translation, human translation, comparison, linguistics